Forecasting Stock Price of PT. GoTo Gojek Tokopedia Tbk (GOTO.JK) using ARIMA Box-Jenkins Method - Saputra, Julian (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2024)
PT. GoTo Gojek Tokopedia Tbk, formed through the merger of Indonesian tech giants Gojek and Tokopedia, is a leading digital technology company. It offers diverse services including logistics, financial services, e-commerce, and food delivery. Operating both domestically and internationally, it continues to innovate its products and services, playing a pivotal role in shaping the digital economy landscape in Indonesia and beyond. Will use ARIMA (p,d,q) technical analysis to predict the stock price of The forecasting of stock price of PT. GoTo Gojek Tokopedia Tbk for the next 10 weeks from March 06, 2023 to May 8, 2023. The researchers used PT. GoTo Gojek Tokopedia Tbk historical stock price data from April 11, 2022 to February 27, 2023. Based on the test result of all the ARIMA Models, the best model that the researcher got is Model 3 ARIMA (2,1,2). This model is taken as the best model because the model has the smallest MSE Value of 106.36830; the RMSE Value of 0.07845252; the MAE value of 8.07106; and the smallest MAPE Value of 7.84525%. It shows that that the stock price is predicted to rise for the next 10 weeks.